Antigen Specific Regulatory T Cells in Kidney Transplantation and Other Tolerance Settings - Hu, Min; Rogers, Natasha M.; Li, Jennifer; Zhang, Geoff Y.; Wang, Yuan Min; Shaw, Karli; O’Connell, Philip J.; Alexander, Stephen I. (Frontiers in Immunology, 2021)
Kidney transplantation is the best current therapy for end-stage kidney failure. However, with standard immunosuppression, most transplants develop chronic dysfunction or fail, much of which is due to chronic immune injury. Tregs are a subset of T cells involved in limiting immune activation and preventing autoimmune disease. These cells offer the potential to provide tolerance or to allow reduction in immunosuppression in kidney transplants. The importance of Tregs in kidney transplantation has been shown in a number of seminal mouse and animal studies, including those with T cell receptors (TCRs) transgenic Tregs (TCR-Tregs) or Chimeric Antigen Receptor (CAR) Tregs (CAR-Tregs) showing that specificity increases the potency of Treg function. Here we outline the animal and human studies and clinical trials directed at using Tregs in kidney transplantation and other tolerance settings and the various modifications to enhance allo-specific Treg function in vivo and in vitro.